Mobile phones and safety in developing countries: Evidence from Sub-Saharan Africa. (June 2015) - James, Jeffrey
Highlights: Safety is the main reason for mobile phone use in a survey of 12 countries in Sub-Saharan Africa. This issue is examined in a range of geographical contexts: non-violent, conflict and post-conflict situations. An explanation of the findings is founded on an interaction of poverty, inequality and crime. One policy conclusion is the need for peace huts that are linked to the police in the country concerned. Abstract: This paper is concerned with the relationship between safety and mobile phones with particular reference to Sub-Saharan Africa; and looks at a range of geographical contexts: non-violent, conflict and post-conflict situations. The main part of the paper reports on recent findings of extensive field-work into the use of mobile phones in 11 countries in Sub-Saharan Africa. The findings are important partly because from a welfare view, it is use rather than mere adoption that generates actual benefits to consumers. What the survey finds is that use of the mobile phone is mainly for safety-related purposes and that the countries that fare highest in terms of usage are drawn from the richest and poorest members of the sample. In explaining these results I draw heavily on the relationships and interactions between poverty, inequality and crime. For example, the dominance of Southern African countries is ascribed to their exceptionally high levels of inequality, which, in turn, are due partly to the unequal effects of resource abundance.